JSPS-2 Risk of FMD Importation Through Cattle Movement at the Thailand-Myanmar Border: A Preliminary Quantitative Risk Assessment Result - Anuwat Wiratsudakul; Phrutsamon Wongnak; Terdsak Yano; Satoshi Sekiguchi (Hemera Zoa, 2018)
Foot-and-mouth disease (FMD) is an important viral infection affecting productivity performance of many livestock species including cattle. Beef cattle are still traditionally raised in Thai households with small number of animals per family. However, a number of cattle are imported from neighboring countries, especially Myanmar. This importation is managed to supply the needs of domestic consumption and also to convey animals to the third countries.Tak, a Thailand-Myanmar border province, is a major gateway importing cattle from Myanmar. The animals imported into the province are then widely distributed to different regions of Thailand [1]. Therefore, FMD virus may move across the border and further disseminate across the country.The present study hence tried to comprehend the cattle importation process and employed risk assessment technique to quantify the risk of FMD importation via transboundary cattle movement.